IOT based Smart Framework for ATM Security with Electricity Saver - Kumar Verma, Deepak; Singh, Karunesh; Srivastav, Ayush; Singh, Vartika (International Journal of Computer Sciences and Engineering, 2022)
ATM machine is a great piece of technology used by millions of people around the world. It makes our daily transactions easier without loading up the banking systems. However, it is important to keep them secure from thefts and other malicious activities. This work deals with the prevention of ATM theft from robbery, so overcome the drawback found in existing technology in our society. Whenever robbery occurs, Vibration sensor is used here which senses vibration produced from ATM machine. Here DC Motor is used for closing the door of ATM when the vibration is sensed, also a buzzer is also used, once the vibration is sensed, beep sound will occur from buzzer. Furthermore, infrared sensor is also used to develop the automatic light switching system. The automatic light switching system will lead to energy saving and efficient energy usage which could benefit every single individual. This system is developed with safety environment, switching the light ‘ON’ or ’OFF’ during entry and exit. In this paper we have proposed a model for smart security and electricity saver system developed with the help of Arduino uno kit and sensors.